Study on Biochemical Changes in Water and Catla Catla Exposed to the Toxicant Cadmium Chloride: The Impact of Cadmium Chloride Exposure on Biochemical Components in Water and Catla Catla (Journal of Advances and Scholarly Researches in Allied Education, 2019)
One of the 23 heavy metal toxicants cadmium (Cd) is commonly utilized for the manufacture, non-corrosive design of Ni-Cd batteries, in the metal mining industries, dentistry. Cd is emitted to soil, surface ground water systems in considerable volumes through industrial effluents. Standard biochemical process in the five tissues, i.e. muscles, gills, liver, cardiac kidney, healthy fish fish exposed to 96 hour LC50 (lethals) sublethals (110th lethal for 7 days of exposure) of cadmium c have been determined by the levels of the 5 biochemical components of glucose, glycogen, total proteins Free aminoacids. Except for glucose, studies indicated that fish grown in aquatic systems close to industrial locations does not have the expected nutritional value. The outcomes showed an important fall in all biochemical elements in all tissues. The high glucose levels seem to indicate the response of the organism to toxic stress. Fish used as food also contributes to heavy metal accumulation in the soft tissues of the body leading to effects of exposure.